Facile synthesis of a high-performance titanosilicate catalyst with controllable defective Ti(OSi)3OH sites. Issue 49 (6th June 2018) - Wu, Lizhi; Tang, Zhimou; Yu, Yunkai; Yao, Xuting; Liu, Wei; Li, Li; Yan, Binghui; Liu, Yueming; He, Mingyuan
Abstract : A facile strategy was carried out to construct a high-performance titanosilicate oxidation catalyst with controllable defective Ti(OSi)3 OH sites. Abstract : A novel TS-1 (TS-1 S ) catalyst with newly-generated defects, i.e. Ti(OSi)3 OH species, which exhibits the highest reactivity among different Ti species, is constructed in an ingenious strategy. This also provides a promising way to effectively tune the intrinsic nature of Ti active centres in other titanosilicates.